Parent coaches` experiences and insights into a youth soccer program - Kerins, A.; Fernandez, M.; Shinew, K. (Journal of Amateur Sport, 2017)
Municipal governments continue to struggle with decreased funding. In order to offset depleting funds, agencies rely on volunteers to provide resources to the public. In youth sport programs, parents provide much of the support, and it is estimated that 90% of youth sport coaches are parents. Given that parents have been instrumental in youth sport programs, the purpose of this study was to understand parents` experiences and insights associated with volunteering by using a youth soccer program located in a mid-sized town in Illinois as a case-study. Specifically, the study examined (a) parents` motivations in volunteering, (b) challenges parent coaches faced while volunteering, and (c) parent coaches` recommendations to agency personnel. Using a purposive sample, 11 parents were interviewed. Findings indicated that parents were motivated to volunteer in order to help their child, and several expressed a more in-depth philosophy about giving back to the community. The primary motivation and benefit for volunteer coaches was their relationships with the children. Relationships with other adults in the program were also significant, but they tended to be secondary. Challenges in volunteering included working with the children, parents, and agency staff. Agency recommendations included providing incentives to coaches, conducting player assessments, ensuring that recruited volunteers share the agency`s philosophy, and addressing volunteer concerns.